Le Canada et la politique étrangère de la France, 1945-1962 : stratégies d'une puissance moyenne - Beauregard, Daniel (Université de Montréal, 2012)
This study questions Canadian international influence during the "Golden Age" by providing a case study of Canada's foreign policy in its relations with France. Multilateral institutions were the cornerstone of Canadian foreign policy; they were providing the politico-economic counterweights allowing Canadians to distance themselves from the United States. These institutions were often perceived as a constraint by the French, who consequently tried to weaken or reform them. Meanwhile, they were trying to preserve their colonial empire and were demanding unanimous occidental support. France became the most disturbing of Canada's allies, almost systematically attacking its foreign policy project, which consisted in trying to balance a firm commitment to NATO and an overtly anti-imperialist policy designed to seduce non aligned countries of the Commonwealth. This dissertation studies the strategies of a "middle power" trying to defuse the crisis between its allies and to reconcile the contradictory dimensions of its own external policy.
Keywords: Atlanticism; Atlantisme; Canada; Commonwealth; Decolonization; Décolonisation; France; History - Canadian / Histoire - Canadienne (UMI : 0334); Middle power; Multilateralism; Multilatéralisme; NATO; OECE; OEEC; ONU; OTAN; Puissance moyenne; UN